Impacts of COVID-19 Regime on Labor Within Food Systems: Whither BRICS Now and Beyond? - Amusan, L.; Okorie, V. O. (My University, 2022)
The advent of COVID-19 has reconfigured foodscape across the globe, BRICS inclusive. Some of the familiar sites where people in BRICS found food in pre-pandemic period has become increasingly threatened while many have completely disappeared, leaving behind dark food deserts. Information on the extent of the devastation caused by the pandemic is still emerging. Such information is pivotal to the articulation of affirmative programs and policies. This article, therefore, explores the impact of the pandemic on food systems of BRICS to indicate how the alliance may positively influence the repositioning of each country member’s foodscape to achieve food security both now and beyond this pandemic. This article uses content analysis of relevant documents and draws from functionalist’s perspective to outline various impacts of the pandemic on food systems. It argues that creating enabling environment for labor, making food security a common goal of BRICS as a body as well as putting in place mechanisms supporting local food systems will invariably ensure food security across various levels in BRICS.
Keywords: BRICS; food security; foodscapes; COVID-19 pandemic; labor; functionalist theory